2022
DOI: 10.1080/21655979.2022.2084246
|View full text |Cite
|
Sign up to set email alerts
|

LINC00514 facilitates cell proliferation, migration, invasion, and epithelial-mesenchymal transition in non-small cell lung cancer by acting on the Wnt/β-catenin signaling pathway

Abstract: The long non-coding RNA (lncRNA) LINC00514 was identified to play an essential oncogenic function in different human cancers, but its effects in non-small cell lung cancer (NSCLC) are yet to be elucidated. In this study, we evaluated the function of LINC00514 in NSCLC. LINC00514 expression and prognosis in NSCLC were analyzed using qRT-PCR and online bioinformatic tools. The bioeffects of LINC0514 in NSCLC cells were examined using cell counting kit-8, colony formation, and transwell assays. Western blotting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…LINC00514 has been shown to be overexpressed in cervical squamous cell carcinoma, gastric cancer, breast cancer and pancreatic cancer [ [77] , [78] , [79] , [80] ]. Zhu et al [ 44 ] indicated that LINC00514 was significantly upregulated in NSCLC and related to poorer prognosis. They observed that silencing LINC00514 decreased the epithelial mesenchymal transition (EMT)-related proteins (E-Cadherin) and Wnt/β-catenin signaling related proteins (β-catenin, cyclinD), while enhancing N-Cadherin expression.…”
Section: Interactions Between Lncrnas and Wnt Signaling Pathway In Lcmentioning
confidence: 99%
See 2 more Smart Citations
“…LINC00514 has been shown to be overexpressed in cervical squamous cell carcinoma, gastric cancer, breast cancer and pancreatic cancer [ [77] , [78] , [79] , [80] ]. Zhu et al [ 44 ] indicated that LINC00514 was significantly upregulated in NSCLC and related to poorer prognosis. They observed that silencing LINC00514 decreased the epithelial mesenchymal transition (EMT)-related proteins (E-Cadherin) and Wnt/β-catenin signaling related proteins (β-catenin, cyclinD), while enhancing N-Cadherin expression.…”
Section: Interactions Between Lncrnas and Wnt Signaling Pathway In Lcmentioning
confidence: 99%
“…For instance, LINC00514 increases the migration and invasion of NSCLC. On the one hand, LINC00514 silencing reduced TCF/LEF1 activity, demonstrating yet another way that LINC00514 knockdown inactivated Wnt signaling in NSCLC cells; on the other hand, down-regulation of LINC00514 inhibited migration and invasiveness abilities of cells and tumor xenograft growth [ 44 ]. The Wnt/β-catenin pathway is recognized as carcinogenic.…”
Section: Biological Functions Of Lncrnas/wnt/β-catenin Axis In Lcmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the standard primary therapy for patients with SCLC has been the combination chemotherapy of etoposide and platinum 3 , 17 . Despite the initially high response rate, a significant number of patients experience rapid progression.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the initially high response rate, a significant number of patients experience rapid progression. More recently, the addition of immune checkpoint inhibitors (such as atezolizumab or bevacizumab) to platinum-etoposide therapy in ES-SCLC patients has shown a transformative effect on OS, leading to a significant paradigm shift in the primary treatment model for SCLC 3 , 17 .…”
Section: Introductionmentioning
confidence: 99%